PERANAN PENYULUHAN TERHADAP PERSEPSI MASYARAKAT BEROBAT KE PUSKESMAS TENAYAN RAYA - R. Sri Ayu Indrapuri; Anastasya Shinta Yuliana; indah jailani; hafizah (Awal Bros Journal of Community Development, 2021)
Public health is one of the important priorities that the government always pays attention to. Not without reason, a good level of public health will certainly have a positive influence on a prosperous life. Where a healthy community can perform various activities well. One of the ways to support optimal health is to provide health services, one of which is Public health center. The public perception about the Public health center is that there are still people who do not understand the importance of going to the Public health center. The problems faced at this time are the attitude that is less responsive to patients, less friendliness than the provision of services needed by the community, so that people feel dissatisfied every time they go to the hospital. Public health center. This is indicated by the number of complaints from the community both from health services and facilities and infrastructure at the Public health center and there are also complaints from the community about not recovering from their illness so that they do not want to go to the Public health center and choose other alternatives. This activity was carried out on Saturday, November 13, 2021 in the community area of ​​RW 004 Kulim Village, Kulim District Using lecture and question and answer methods. As for the results of this outreach activity, the community has been able to understand and change public perceptions regarding the importance of going to the Public health center for treatment. And the community also quite understands how important it is to go to the health center and want to go back for treatment to the health center without any worries.